Immediate Effect of Thoracic Spine and Shoulder Joint Manipulation and Thermotherapy on Glenohumeral Range of Motions in Patients with Adhesive Capsulitis: Life Sciences-Physiotheraphy - Kalita, Abhijit; Sarma, Pratap Chandra; Saikia, Jayanta Madhab; Dutta, Abhijit; K Rajak, Santosh (International Journal of Life Science and Pharma Research, 2022)
Adhesive capsulitis (AC) is a common shoulder condition that leads to progressive loss of shoulder joint mobility leading to functional limitations. Many treatment protocols are in practice however there is no consensus on which is the best. Much literature reflects clinicians using thoracic spine and shoulder joint manipulations in different studies but a lack of evidence was found studying their effect when applied together and their immediate effect, for the management of patients with AC. Therefore, the objective of this study was to statistically analyse and report the immediate effect of thoracic spine and shoulder joint manipulations on subjects with AC assessing their pain and joint Range of motion. In this study, purposive sampling of 20 pre diagnosed subjects of AC were included and VAS conducted a pre-intervention assessment for assessing pain, and a goniometer for assessing the glenohumeral active Range of motion. All the subjects received a single session of high-velocity thrust manipulative therapy to the cervicothoracic junction, upper/mid-thoracic spine, and the glenohumeral joint of the affected shoulder. Everyone received thermotherapy (moist heat) before and after the manual therapy session, after which the data were documented and analyzed statistically. It was observed that there was a significant difference between pre and post-VAS and pre and post-range of motion scores in the samples (p<0.001). It is essential to mention that compared to VAS, goniometry results were more promising. To conclude, it can be stated that thoracic spine and shoulder joint manipulation adjunct with thermotherapy, in general, has an immediate positive effect on the management of patients with adhesive capsulitis.